2000
DOI: 10.1017/s0003598x00059883
|View full text |Cite
|
Sign up to set email alerts
|

The man, the woman and the hyoid bone: from archaeology to the burial practices of the Xiongnu people (Egyin Gol valley, Mongolia)

Abstract: A man and a woman were found in a double burial dating from the 1st century BC and located in a Xiongnu burial site in northern Mongolia. An offering box at the head of the man's coffin contained both remains of domestic animals and a human hyoid bone. The skeleton of the man was complete whereas the woman's hyoid bone was missing. The isolated hyoid bone could belong to the buried woman, which suggests the removal of her tongue and probably her sacrifice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…At a short distance from him, a privileged man was also buried (grave 27), as were other individuals, including those found in double graves (graves 32/32A, 33/33A, 37/ 37A, and 38/38A). Some of these surrounding graves could be sacrificial burials, as has been reported elsewhere for one of them (Murail et al 2000). This tradition of having double graves near an opulent one in cemeteries containing individuals of high social class is well documented, notably in the Sakka (another group of nomadic people of the Eurasian steppes) and the Pazyryk cultures (Francfort et al 2000).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…At a short distance from him, a privileged man was also buried (grave 27), as were other individuals, including those found in double graves (graves 32/32A, 33/33A, 37/ 37A, and 38/38A). Some of these surrounding graves could be sacrificial burials, as has been reported elsewhere for one of them (Murail et al 2000). This tradition of having double graves near an opulent one in cemeteries containing individuals of high social class is well documented, notably in the Sakka (another group of nomadic people of the Eurasian steppes) and the Pazyryk cultures (Francfort et al 2000).…”
Section: Discussionmentioning
confidence: 58%
“…2, 3, and 4). The southern sector (A) was composed of four double graves (32/32A, 33/33A, 37/37A, and 38/38A), each of which contained two sets of remains that were probably buried within the same period (Murail et al 2000). Grave 27 was surmounted by a standing stone and was found to conceal exceptional furniture.…”
Section: Sitementioning
confidence: 99%
“…The low-burial frequency (0.25 burial per year), funerary artifacts and practices (use of coffins and chests, depth of the graves at two-five meters, animal sacrifices, etc. ), and the genetic analysis of human remains suggested that this burial site was used by high-social-status individuals representing only a subset of the whole Xiongnu community (Crubézy et al, 1996;Murail et al, 2000;Keyser-Tracqui et al, 2003). The extent of epiphyseal fusion and spheno-occipital synchondrosis was used to determine the subadult and adult status of all individuals.…”
Section: Materials Samplesmentioning
confidence: 99%
“…The Egiin Gol sample comes from the Borkhan Tolgoi cemetery, which has been previously studied (Murail et al, 2000;Keyser-Traqui et al, 2003;Wright, 2006;Wright et al, 2009;Ricaut et al, 2010). This necropolis was used during the entire Xiongnu period and contains the remains of 84 graves containing skeletal material from 99 individuals (Fig.…”
Section: "Local" Level Analysis Suggests Possible Population Structurmentioning
confidence: 99%
“…It was arranged into three main sections that roughly correspond to temporal ordering. Section A is the oldest followed by Section B and Section C. Section A contains a number of "double burials" near graves marked with higher status individuals (Murail et al, 2000). This practice was quite common among peoples of the Scytho-Siberian tradition, including the Yakuts and the Bronze Age Pazyryk culture of the Gorny Altai in southern Siberia (Chikisheva, 2000(Chikisheva, , 2008Ricaut et al, 2004aRicaut et al, , 2004bAmory et al, 2006).…”
Section: "Local" Level Analysis Suggests Possible Population Structurmentioning
confidence: 99%